The Influence of Concentration and Type of Salts on the Behaviour of Linear Actuators Based on PVA Hydrogel Activated by AC Power - Aleksey Maksimkin; Mikhail Zadorozhnyy; Kseniia V. Filippova; Lidiia D. Iudina; Dmitry V. Telyshev; Tarek Dayyoub (Gels, 2025)
The creation of quick-reacting electrically conductive polymers for use as actuators driven by low electrical currents is now seen as an important issue. Enhancing the electrical conductivity of hydrogels through the incorporation of conductive fillers, like salts, can reduce the necessary actuating voltage. However, several important questions arise about how the type of salt chosen and its concentration will affect not only the activation efficiency of the actuators but also the structure of the hydrogels utilized. In this study, to enhance the electrical conductivity of the hydrogel and lower the necessary activation voltage of the hydrogel actuators, lithium chloride (LiCl) and sodium chloride (NaCl) were incorporated as conductive fillers into the polyvinyl alcohol (PVA) polymer matrix. To determine the deformation of actuators, as well as the activation and relaxation times and efficiencies during activation, linear actuators capable of being activated through extension/contraction (swelling/shrinking) cycles were developed and examined based on the LiCl/NaCl content, applied voltage, and frequency. The main finding is that the required actuating voltage was lowered by up to 20 V by adding an equal mass of salt in relation to the PVA mass content. With a load of around 20 kPa, it was observed that the extension deformation for PVA/NaCl-based actuators can achieve 75%, while in contraction deformation, can reach 17%. Additionally, for the PVA/LiCl-based actuators, the extension deformation can reach 87%, while during contraction deformation, it can reach 22%. The degree of swelling in the PVA/NaCl hydrogels was generally less than that in the PVA/LiCl hydrogels, which was associated with the finding that the actuators prepared from PVA/NaCl hydrogels delivered an output that was 10–15% lower than those made from PVA/LiCl hydrogels across different testing cycles. Furthermore, adding salt increases the degree of crosslinking, which can explain why increased crosslinking leads to reduced deformation when exposed to AC voltage. These actuators can find extensive use in soft robotics, artificial muscles, medical applications, and aerospace industries.